Interdependence Between the Tourist Regions of Sergipe, Brazil - Ribeiro , Luiz Carlos de Santana; Carvalho , Daniel Silva Antunes de; Lopes, Thiago Henrique Carneiro Rios; Sousa Filho, José Firmino de (REGION, 2024)
We constructed an interregional input-output system for the tourist regions of Sergipe and identified the contribution of Tourism Characteristic Activities (TCAs) to the state’s economy. It is the first system built for tourist regions in Brazil that disaggregates tourism activities by sector and region, representing a novel approach in Brazilian literature. By measuring the weight of tourist activities, we avoid overestimating tourism in the regional economy. Researchers can use this method for countries and regions that do not have a Tourism Satellite Account. The main results estimate that TCAs in Sergipe accounted for 1.53% of the state’s gross value added (GVA) in 2015, 3.7 times lower when considering only tourism activities. The Polo Costa dos Coqueirais stands out among the tourist regions, particularly regarding the distribution of TCAs’ GVA within the state. Tourist road transportation is considered a key sector in all tourist regions.